Magnetic Field on A Square Helmholtz Coil Experiments Using Remote Laboratory - Ishafit, Ishafit; Kustianingsih, Diah Ayu; Indratno, Toni Kus; Sukarelawan, Moh. Irma (Indonesian Review of Physics, 2024)
This research aims to explore the potential for innovation in physics teaching methods by utilizing remote laboratory technology for square Helmholtz coil magnetic field experiments. This research uses experiments with two variations of the distance between coils, accessed through an online portal-based remote laboratory, and magnetic field data taken using a Vernier magnetic field sensor. The results showed that the remote experiment produced data similar to the analytical predictions, with relative errors of 7.45% and 6.06% for the two different inter-coil distances. In conclusion, remote laboratories have great potential to support innovation in physics teaching methods. This research implies that remote experiments can be an efficient and accurate tool in online physics learning, providing a helpful practicum experience despite being conducted remotely.